On the Fuzzy Extension Principle for LP Problems with Interval Type-2 Technological Coefficients - Figueroa, Juan Carlos (Ingeniería, 2015)
A special kind of Linear Programming (LP) problems involve linguistic uncertainty that can be represented by Interval Type-2 Fuzzy numbers using the extension principle for fuzzy sets. This principle has been widely used in decision making, computation of a function of fuzzy sets, fuzzy optimization, etc, so this paper focuses to clarify some aspects about its use in LPs with interval Type-2 fuzzy technological parameters.